2016
DOI: 10.1253/circj.cj-16-0488
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mechanics of Left Ventriculo-Atrial Coupling in Patients With Diabetic Nephropathy

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp nephropathy has been identified as independently associated with LVSD in asymptomatic DM patients with preserved LVEF. 13- 15 We recently focused our research especially on the interaction of albuminuria and LVSD in such patients, 16 and as a result consider albuminuria to be the primary mediator of myocardial fibrosis by suppression of collagen turnover via impaired crosslinking of collagen. However, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Clinical data showed that the prevalence of dyslipidemia in T2DM patients with overweight was higher than in those without overweight, while echocardiographic data showed that T2DM patients with overweight had a higher LV mass index and lower GLS compared to those without overweight. Intra- and inter-observer reproducibility for GLS for DM patients in our study group was previously reported [ 14 16 , 24 ].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Clinical data showed that the prevalence of dyslipidemia in T2DM patients with overweight was higher than in those without overweight, while echocardiographic data showed that T2DM patients with overweight had a higher LV mass index and lower GLS compared to those without overweight. Intra- and inter-observer reproducibility for GLS for DM patients in our study group was previously reported [ 14 16 , 24 ].…”
Section: Resultsmentioning
confidence: 60%
“…Independent associations of GLS with clinical and echocardiographic parameters in T2DM patients were evaluated by means of multiple regression analysis. The confounding factors for multiple regression analysis were based on the associated factors with subclinical LV dysfunctions in DM patients with preserved LVEF which were previously reported [ 14 , 15 , 24 ]. Statistical significance for each step was basically defined as p value < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Although the exact causes leading to the LV changes in patients with T2D remain still unclear, the reduction of coronary flow reserve, metabolic abnormality, autonomic dysfunction, and myocardial fibrosis have been reported as possible mechanisms of subclinical myocardial damage [24]. Besides these data, subclinical LA structural and functional changes are also known to be common findings in patients with T2D [2527]. Interestingly, Wang et al reported that LA energy loss and deformation mechanics are already impaired even in T2D patients with normal LA size [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, left atrial volume index was the independent determinant parameter for GLS as well as T2DM and LVEF. It is considered that LV longitudinal myocardial function is closely related to left atrial function (LV size) [10]. Impairment of GLS led to a decrease in the force of drawing the LV basal plane in systole, and this mechanical link to insufficient pulling of the left atrium into the apex.…”
Section: T2dm and Dcmmentioning
confidence: 99%